Exceptional topological insulators - M. Michael Denner (Nature Portfolio, 2021)
Three-dimensional topological insulators have become a research focal point on topological quantum matter. Here, the authors propose the non-Hermitian analogue, the exceptional topological insulator, with anomalous surface states only existing within the topological bulk embedding.